Information Network Crimes in China: An Analysis Regarding the Contemporary Juridical Situation and Suggestions for Future Improvements - Chen, Qiange; Yan, Yinxun (International Journal of Social Sciences and Public Administration, 2024)
The focalization of this article is the current situation of criminal justice regarding information network crimes, the potential solutions for foreseen challenges, as well as suggestions for future improvements. This essay has clearly introduced the background information under the topic and pointed out the existing challenges regarding the juridical situation in China. Within high percentages illustrated, the criminal prosecution rate and guilty sentence rate in China concerning the criminal offences in information network crimes have raised another series of societal problems and concerns, which are negatively influencing the fairness of legal justice. Meanwhile, the crucial factor of “knowing” determines if a suspect is convictable to a criminal court, but the realistic cases have reflected that this factor is typically affirmed arbitrarily. Thus, this article also addressed the existing problems regarding law enforcement and realistic cases, especially the crucial factor of “knowing”.